2003
DOI: 10.1016/s1383-5718(03)00032-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of haemoglobin in the protection of cultured lymphocytes against diepoxybutane (DEB), assessed by in vitro induced chromosome breakage

Abstract: Diepoxybutane (DEB) is an alkylating agent that can be used to assess chromosome instability in repair-deficient subjects. Previous authors investigated the role of red blood cells (RBC) in determining individual susceptibility to DEB in normal healthy donors, and demonstrated that a polymorphic enzyme in RBC, Glutathione S-transferase T1 (GSTT1), is involved in DEB detoxification. In the present work we studied the influence of individual GSTM1 and GSTT1 genotypes and the presence of RBC on the frequency of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Our results are in accordance with the studies which found a negative correlation between hemoglobin level and DNA damage [9], and with the studies that showed protection by normal RBC [10] or fetal RBC [21] of lymphocytes against chromosomal breakage induced in lymphocytes by the alkylating agent diepoxybutane. Similar to our findings, Porto et al suggested that this effect is obtained by hemolysed RBC and more specifically by the hemoglobin [10].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in accordance with the studies which found a negative correlation between hemoglobin level and DNA damage [9], and with the studies that showed protection by normal RBC [10] or fetal RBC [21] of lymphocytes against chromosomal breakage induced in lymphocytes by the alkylating agent diepoxybutane. Similar to our findings, Porto et al suggested that this effect is obtained by hemolysed RBC and more specifically by the hemoglobin [10].…”
Section: Discussionsupporting
confidence: 93%
“…Similar to our findings, Porto et al suggested that this effect is obtained by hemolysed RBC and more specifically by the hemoglobin [10]. They further suggested an additional protective effect of fetal RBC due to increased antioxidative activity by the increased glutathione transferase, catalase and superoxide dismutase activity in fetal RBC [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consequently, cell protective systems against oxidative stress are involved in DEB detoxification, with red blood cells (RBC), or some of its components in particular, playing an important role. In a previous study, we have shown that RBCs can protect cultured lymphocytes against chromosomal breaks induced by DEB (21). In a previous study, we have shown that RBCs can protect cultured lymphocytes against chromosomal breaks induced by DEB (21).…”
Section: Introductionmentioning
confidence: 90%
“…It was found that the glutathione S-transferase gene GSTT1 (expressed in RBC) was involved in determining sensitivity of lymphocytes to DEB-induced chromosome aberrations (Porto et al, 2003). This may have important clinical implications in recovering the hematological status of FA patients and reducing chromosome instability (Porto et al, 2010).…”
Section: Resultsmentioning
confidence: 99%